Hodgkin's lymphoma: the pathologist's viewpoint. Issue 3 (1st March 2002) - Pileri, S A; Ascani, S; Leoncini, L; Sabattini, E; Zinzani, P L; Piccaluga, P P; Pileri, A; Giunti, M; Falini, B; Bolis, G B; Stein, H
Abstract : Despite its well known histological and clinical features, Hodgkin's lymphoma (HL) has recently been the object of intense research activity, leading to a better understanding of its phenotype, molecular characteristics, histogenesis, and possible mechanisms of lymphomagenesis. There is complete consensus on the B cell derivation of the tumour in most cases, and on the relevance of Epstein-Barr virus infection and defective cytokinesis in at least a proportion of patients. The REAL/WHO classification recognises a basic distinction between lymphocyte predominance HL (LP-HL) and classic HL (CHL), reflecting the differences in clinical presentation and behaviour, morphology, phenotype, and molecular features. CHL has been classified into four subtypes: lymphocyte rich, nodular sclerosing, with mixed cellularity, and lymphocyte depleted. The borders between CHL and anaplastic large cell lymphoma have become sharper, whereas those between LP-HL and T cell rich B cell lymphoma remain ill defined. Treatments adjusted to the pathobiological characteristics of the tumour in at risk patients have been proposed and are on the way to being applied.